Concept of organizational and financial provision of sustainable development of territorial entities in the innovation economy - E. F. Nikitskaya; M. A. Valishvili (Путеводитель предпринимателя, 2020)
The article analyzes the conceptual bases, organizational forms and sources of financing of innovative development of regions and municipalities. An innovative model is considered as a system that provides the sustainable development of the national economy.